Project for the Notification and Follow-up of COVID-19 at Hospital CUF Sintra: Projeto de Notificação e Seguimento da COVID-19 no Hospital CUF Sintra - Mora, Patrícia; Lagoa, Matilde; Baltazar, Carolina; Carvalho, Diogo; Câmara, Gonçalo da; Modesto, Filipe; Pohle, Catarina; Fernandes, Sandra; Salvador, Patrícia; Sousa, Inês de; Guerreiro, André; Faustino, Francisco; et al. (Gazeta Médica, 2020)
First discovered in the Chinese province of Wuhan, in early December 2019, the infection by the new coronavirus led to a pandemic prompting the declaration of an International Public Health Emergency by the World Health Organization on the 30th of January 2020. In Portugal, the first cases date from the 3rd of March 2020 with more than 24 600 positive cases of the 247 000 suspected cases within only two months. Given the seriousness of the situation, a National State of Emergency was declared on the 18th of March and extended on April 2nd and 17th 2020. Consequently, and according to the official statement issued by NOVA Medical School in accordance with the previous statement from the NOVA University of Lisbon and the Council of Portuguese Medical Schools regarding the containment measures to be implemented, all clinical practise activities were suspended. In light of this reality, the senior year finalists revealed motivation in playing an active role during the outbreak, showing availability to collaborate with the local authorities and health professionals. A partnership was hence established with the José de Mello Saúde/CUF Health Unit, that supported this initiative by integrating students at the CUF Sintra Hospital (one of its COVID-free units) in administrative tasks under guidance and tutoring of Patrícia Mora, MD. The project started on the 31st of March 2020, with the students collaborating in case notifications on the platform of the National Epidemiological Surveillance System, an instrument that has been essential in collecting representative data for the elaboration of national response strategies, and later updating the internal database. This project contributed to significantly reduce the administrative burden of health professionals with appreciable gains in the availability of doctors and nurses for the assistance and provision of differentiated care and follow-up of clients with or without infection with the new coronavirus